Adenosine increases LPS‐induced nuclear factor kappa B activation in smooth muscle cells via an intracellular mechanism and modulates it via actions on adenosine receptors. (28th October 2013) - Yang, J.; Zheng, X.; Haugen, F.; Darè, E.; Lövdahl, C.; Schulte, G.; Fredholm, B. B.; Valen, G.
Abstract Aim In inflamed and damaged cardiovascular tissues, local extracellular adenosine concentrations increase coincidentally with activation of the transcription factor nuclear factor kappa B (NFκB). To investigate whether adenosine influences NFκB activation in vascular smooth muscle cells (VSMCs) and, if so, to examine the role of its receptors. Methods VSMCs were isolated from NFκB–luciferase reporter mice, cultured and then treated by lipopolysaccharide (LPS) to activate NFκB signalling. Adenosine, adenosine receptor agonists and antagonists, adenosine deaminase and uptake inhibitors were used together with LPS to evaluate the role of adenosine and its receptors on NFκB activation, which was assessed by luciferase activity and NFκB target gene expression. Results Adenosine potentiated LPS‐induced NFκB activation. This was dependent on adenosine uptake and enhanced by an adenosine deaminase inhibitor, suggesting that intracellular adenosine plays an important role. Non‐selective adenosine receptor agonists (2Cl‐Ado and NECA) inhibited NFκB activation induced by LPS. Selective A1 or A2A antagonist given alone could not completely antagonize the NECA effect, indicating that the inhibitory effect was due to multiple adenosine receptors. The activation of the A3 receptor further increased LPS‐induced NFκB activation. Conclusions Adenosine increases LPS‐induced nuclear factor kappa B activation in smooth muscle cells via an intracellular mechanism and decreases it via actions on A1 and A2A receptors. These results provide novel insights into the role of adenosine as a regulator of inflammation‐induced NFκB activation.